# what did they say about the man who died from drinking shellac

Hi, this post is about “what did they say about the man who died from drinking shellac”. Stay tuned to negarinfo for more posts 🌼

## What did they say about the man who died from drinking shellac?

He had a lovely finish.

_______________________________

(x + 4)(x + 2)

Multiplying the binomials by distributing them,

we get;

= x² + 2x + 4x + 8

Adding up the like terms.

= x² + 6x + 8

The answer refers to the letter choice H.

_______________________________

(x + 7)(x + 1)

Multiplying the binomials by distributing them,

we get;

= x² + 7x + 1x + 7

Adding up the like terms.

= x² + 8x + 7

The answer refers to the letter choice E.

_______________________________

(x – 6)(x – 3)

Multiplying the binomials by distributing them,

we get;

= x² – 3x – 6x + 18

Adding up the like terms.

= x² – 9x + 18

The answer refers to the letter choice H.

_______________________________

(x + 8)(x – 2)

Multiplying the binomials by distributing them,

we get;

= x² – 2x + 8x – 16

Adding up the like terms.

= x² + 6x – 16

The answer refers to the letter choice A.

_______________________________

(x – 7)(x + 4)

Multiplying the binomials by distributing them,

we get;

= x² + 4x – 7x – 28

Adding up the like terms.

= x² – 3x – 28

The answer refers to the letter choice D.

_______________________________

(x – 2)(x – 9)

Multiplying the binomials by distributing them,

we get;

= x² – 9x – 2x + 18

more :  what was one action that progressives took to help poor people

Adding up the like terms.

= x² – 11x + 18

The answer refers to the letter choice A.

_______________________________

(2u + 4)(u + 1)

Multiplying the binomials by distributing them,

we get;

= 2u² + 2u + 4u + 4

Adding up the like terms.

= 2u² + 6u + 4

The answer refers to the letter choice L.

_______________________________

(3u + 7)(u – 3)

Multiplying the binomials by distributing them,

we get;

= 3u² – 9u + 7u -21

Adding up the like terms.

= 3u² – 2u – 21

The answer refers to the letter choice O.

_______________________________

(4u – 2)(5u – 1)

Multiplying the binomials by distributing them,

we get;

= 20u² – 4u – 10u + 2

Adding up the like terms.

= 20u² – 14u + 2

The answer refers to the letter choice V.

_______________________________

(2u + 1)(9u – 5)

Multiplying the binomials by distributing them,

we get;

= 18u² – 10u + 9u – 5

Adding up the like terms.

= 18u² – u – 5

The answer refers to the letter choice E.

_______________________________

(7u – 4)(3u + 6)

Multiplying the binomials by distributing them,

we get;

= 21u² + 42u – 12u – 24

Adding up the like terms.

= 21u² + 30u – 24

The answer refers to the letter choice L.

_______________________________

(5u – 8)(4u – 4)

Multiplying the binomials by distributing them,

we get;

= 20u² – 20u – 32u + 32

Adding up the like terms.

= 20u² – 52u + 32

The answer refers to the letter choice Y.

_______________________________

(2x + y)(x + 3y)

Multiplying the binomials by distributing them,

we get;

more :  a garbage dumping placard must be prominently

= 2x² + 6xy + 1xy + 3y²

Adding up the like terms.

= 2x² + 7xy + 3y²

The answer refers to the letter choice F.

_______________________________

(3x – y)(8x – y)

Multiplying the binomials by distributing them,

we get;

= 24x² – 3xy – 8xy + y²

Adding up the like terms.

= 24x² – 11xy + y²

The answer refers to the letter choice I.

_______________________________

(2x + y)(4x – 3y)

Multiplying the binomials by distributing them,

we get;

= 8x² – 6xy + 4xy – 3y²

Adding up the like terms.

= 8x² – 2xy – 3y²

The answer refers to the letter choice N.

_______________________________

(5x – 2y)(3x + 4y)

Multiplying the binomials by distributing them,

we get;

= 15x² + 20xy – 6xy – 8y²

Adding up the like terms.

= 15x² + 14xy – 8y²

The answer refers to the letter choice I.

_______________________________

(7x + 3y)(x + 2y)

Multiplying the binomials by distributing them,

we get;

= 7x² + 14xy + 3xy + 6y²

Adding up the like terms.

= 7x² + 17xy + 6y²

The answer refers to the letter choice S.

_______________________________

(6x + 6y)(2x – 4y)

Multiplying the binomials by distributing them,

we get;

= 12x² – 24xy + 12xy – 24y²

Adding up the like terms.

= 12x² – 12xy – 24y²

The answer refers to the letter choice H.

more :  credits beyond degree example